Water extractable organic carbon and nitrogen and their stable isotopes from long-term experiment in a Japanese rice paddy - Toan Nguyen-Sy; Weiguo Cheng; Julien Guigue; Samuel Munyaka Kimani; Wisnu Aji Wibowo; Keitaro Tawaraya; Toru Watanabe; Ji Wu; Xingkai Xu (Journal of Wetlands Environmental Management, 2018)
Hot water- and water-extracted organic matter was extracted from soil samples collected after a 31-year long-term experiment which aimed to assess the effect of different fertilization strategies (inorganic fertilizers and organic matters) commonly used for paddy rice cultivation in Yamagata, northeastern Japan. The ratio of soil to extracted water was 2:3. The amounts of hot water-extracted organic carbon and nitrogen (HWEOC and HWEN) at 80 oC and 16 hours, water-extracted organic carbon and nitrogen (WEOC and WEN) at room temperature, and their δ13C and δ15N were measured from the five fertilizer treatment plots as [1) PK, 2) NPK, 3) NPK + 6 Mg ha-1 rice straw (RS), 4) NPK + 10 Mg ha-1 rice straw compost (CM1), and 5) NPK + 30 Mg ha-1 rice straw compost (CM3)], for surface (0-15 cm) and subsurface (15-25 cm) layers. HWEOC and WEOC accounted for an average of about 1.51 and 0.66% of SOC, while HWEN and WEN accounted for an average of about 1.09 and 0.40% of soil TN, respectively. About 90% of the extracted N was organic form among all treatments. The values of δ13C for HWEOC and WEOC ranged from -28.2 to -26.5‰ and from -28.3 to -27.0‰, similar to the original rice straw and rice straw compost, and lower than the value of original soil at -22.5‰. The values of δ15N of HWEN, WEN and bulk soil ranged from 0.8 to 3.8‰, from 1.0to 4.0‰, and from 0.8 to 2.8‰, respectively. It was clear that δ15N decreased in RS but increased in CM3 treatments. Our results indicated that the amounts of hot water- and water-extracted organic matter were affected by long-term application of inorganic fertilizers and organic matters remarkably. However, the values of δ13C for HWEOC and WEOC were not different among 5 treatments, but values of δ15N of HWEN and WEN were affected by RS and CM3 applications clearly.